Role of fatty acids in Bacillus environmental adaptation - Diomande, Sara E.; NGUYEN-THE, Christophe; Guinebretière, Marie-Hélène; Broussolle, Veronique; Brillard, Julien (Frontiers in Microbiology, 2015)
The large bacterial genus genus Bacillus is widely distributed in the environment and is able to colonize highly diverse niches. Some Bacillus species harbour pathogenic characteristics. The fatty acid (FA) composition is among the essential criteria used to define Bacillus species. Some elements of the FA pattern composition are common to Bacillus species, whereas others are specific and can be categorized in relation to the ecological niches of the species. Bacillus species are able to modify their FA patterns to adapt to a wide range of environmental changes, including changes in the growth medium, temperature, food processing conditions, and pH. Like many other Gram-positive bacteria, Bacillus strains display a well-defined FA synthesis II system that is equilibrated with a FA degradation pathway and regulated to efficiently respond to the needs of the cell. Like endogenous FAs, exogenous FAs may positively or negatively affect the survival of Bacillus vegetative cells and the spore germination ability in a given environment. Some of these exogenous FAs may provide a powerful strategy for preserving food against contamination by the Bacillus pathogenic strains responsible for foodborne illness.